2021
DOI: 10.1111/nph.17808
|View full text |Cite
|
Sign up to set email alerts
|

Rht24b, an ancient variation of TaGA2ox‐A9, reduces plant height without yield penalty in wheat

Abstract: Rht-B1b and Rht-D1b, the 'Green Revolution' (GR) genes, greatly improved yield potential of wheat under nitrogen fertilizer application, but reduced coleoptile length, seedling vigor and grain weight. Thus, mining alternative reduced plant height genes without adverse effects is urgently needed.We isolated the causal gene of Rht24 through map-based cloning and characterized its function using transgenic, physiobiochemical and transcriptome assays. We confirmed genetic effects of the dwarfing allele Rht24b with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 61 publications
0
52
1
Order By: Relevance
“…Only a few genes for PH have previously been isolated, including RhtB1b , RhtD1b , Rht8 , Rht24 , and TaWUS-like . The first four genes reduce the PH via the GA pathway, and TaWUS-like may be related to the GA and/or BR pathway [ 6 , 18 , 19 , 20 , 21 ]. In this study, we isolated a novel gene, TaDHL , that controls PH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few genes for PH have previously been isolated, including RhtB1b , RhtD1b , Rht8 , Rht24 , and TaWUS-like . The first four genes reduce the PH via the GA pathway, and TaWUS-like may be related to the GA and/or BR pathway [ 6 , 18 , 19 , 20 , 21 ]. In this study, we isolated a novel gene, TaDHL , that controls PH.…”
Section: Discussionmentioning
confidence: 99%
“…The causal gene of Rht24 , TraesCS6A02G221900 ( TaGA2ox-A9 ), was also isolated, which encodes a gibberellin (GA)2-oxidase. The Rht24b allele was found to confer a higher expression of TaGA2ox-A9 in stems, leading to a reduction in bioactive GA in stems but an elevation in leaves with no yield penalty [ 20 ]. A novel gene, WUS CHEL-related homeobox-like ( TaWUS-like ), was identified that regulates the sheathed spike and plant architecture.…”
Section: Introductionmentioning
confidence: 99%
“…A striking difference to other reported Rht genes in wheat is that Rht13 is not directly involved in GA signalling or metabolism, as is the case for conventional dwarfing genes Rht-B1b and Rht-D1b (Peng et al ., 1999) and the cloned alternative dwarfing genes Rht12 (Buss et al ., 2020), Rht18 (Ford et al ., 2018) and Rht24 (Tian et al ., 2022). Instead, Rht13 is a NB-LRR gene with a point mutation that induces autoactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Map position, allelism tests and increased expression of the same GA 2-oxidase gene in Rht14 lines suggested that Rht14 and Rht18 are allelic (Haque et al ., 2011; Tang, 2016; Ford et al ., 2018). Increased expression of related GA 2-oxidase genes was also found to be responsible for other alternative dwarfing alleles such as Rht12 ( GA2oxA13 on chromosome 5A) (Sun et al ., 2019; Buss et al ., 2020) and Rht24 ( GA2oxA9 on chromosome 6A, not allelic with Rht18 ) (Tian et al ., 2022). These alternative dwarfing genes appear to operate through a shared mechanism, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…These findings have led some to propose that Rht18, Rht24, and Rht14 are allelic (Tian et al, 2017;Würschum et al, 2017;Ford et al, 2018;Mo et al, 2018). Indeed, a recent study confirmed that the transcriptional upregulation of GA2oxA9 explains the effect of Rht24 (Tian et al, 2021b). More intriguingly, the semi-dwarfing Rht24b allele reduces plant height and increases nitrogen use efficiency, but has no yield penalty, illustrating a favorable semi-dwarfing gene (Tian et al, 2021b).…”
Section: Breeding Semi-dwarf Staturementioning
confidence: 99%